Gardening in mosque courtyards: Elderly women’s agency and capabilities in collective practices - Muhammad Ashabul Kahfi; Fitriani Jamaluddin (Interaction, Community Engagement, and Social Environment, 2026)
Background: Older women are often perceived as no longer being socially or economically active. However, in Palopo City, elderly women affiliated with the Nurul Yaqin Mosque have transformed neglected mosque land into a productive garden. This phenomenon demonstrates their agency and highlights how a faith-based social environment can support capability expansion in later life. Drawing on Amartya Sen’s Capability Approach, this study examines how elderly women exercise agency and construct meaningful roles through collective gardening practices. Methods: This qualitative study employed an ethnographic approach. Data were collected through informal interviews with five elderly women actively involved in gardening, participant observation, and supporting documentary sources during an eight-week period between March and May 2025 at the Nurul Yaqin Mosque, Palopo City. Data validity was ensured through source triangulation. Findings: The findings reveal that elderly women participate in gardening for three main reasons: to support household food self-reliance, to utilize their leisure time meaningfully, and to maintain their physical and mental well-being. Gardening also functions as a space for knowledge sharing, social interaction, and the strengthening of social solidarity among participants. Through access to fresh vegetables and stronger social networks, the women experience enhanced well-being, social participation, and expanded capabilities. Nevertheless, they continue to face physical, emotional, environmental, and institutional constraints. The mosque courtyard serves as an enabling social environment that allows elderly women to transform available resources into meaningful functionings, including food production, social participation, and collective contribution to community well-being. Conclusion: This study demonstrates that elderly women are not passive social actors but active agents who expand their capabilities through productive, collective, and faith-based practices. The findings highlight the important role of mosque-based community spaces in supporting active ageing, social participation, and the empowerment of elderly women. Novelty/Originality of this article: This study contributes to the literature by integrating ageing, gender, religion, and Amartya Sen’s Capability Approach, showing how mosque-based environments can facilitate capability expansion, social recognition, and collective empowerment among elderly women in a localized Indonesian context.